ANALYSIS OF SERVICE QUALITY AND APPLICATION QUALITY ON PATIENT LOYALTY IN THE DIGITAL ERA AT CICENDO EYE HOSPITAL, BANDUNG - Indriana, Galih; Suwarsi, Sri; Sumadilaga, Subhan Perkasa (Jurnal Ilmiah Keperawatan, 2025)
Background: Digital-based service quality is an encouragement for consumers to establish strong bonds with the company in the long term. Challenges in hospital service quality and the effectiveness of healthcare applications must be addressed to improve patient loyalty and ensure hospital sustainability. Objective: To determine the effect of service quality and application quality on patient loyalty at the Cicendo Eye Center Hospital, Bandung. Methods: The research method used is descriptive verification. The sample of this study used the purposive sampling technique, where the number of samples was 159 people selected based on criteria. Primary data were collected through questionnaires. Data processing uses regression to test the hypothesis, F-test. Results: The findings show that service quality is rated at a moderate level, application quality is rated at a low level, and patient loyalty at Cicendo Eye Center Hospital, Bandung is also rated at a moderate level. Conclusion: Data gathered under joint testing reveal that measures of service quality and application quality demonstrate a statistically significant positive interaction; each remains influential in its own right. In light of that outcome, the two factors can be said to sway patient loyalty. Given these findings, hospital administrators are urged to reassess their information systems in order to bolster user perception and overall satisfaction.